Analisis Pengembangan Kolaborasi Antara Pemerintah Daerah Dan Pelaku Pariwisata Dalam Pemulihan Ekonomi Kreatif Di Kabupaten Polewali Mandar - Rita Rita; Muhammad Yusuf Yunus (SEIKO : Journal of Management & Business, 2022)
This study aims to determine the collaboration of stakeholders in the recovery of the creative economy in tourist attractions in Polewali Mandar Regency. The research used in this study is a qualitative research with a descriptive approach design. In this study, we used library research methods and field studies through observation, documentation, and interviews. The data analysis used is the Moleong-style data analysis model which includes three stages, namely the data reduction process, data presentation, and conclusion drawing. The stages in this study include the first stage of the orientation process, the second stage of reduction, and the third stage of selection. Then, the validity of the data will be checked using data triangulation techniques, namely source triangulation, technique triangulation, and time triangulation. Organizing carried out by the tourism office in terms of grouping, and regulating activities to achieve the desired goals by dividing the work in operational tasks from both Stakeholders, Creative Economy Actors and MSMEs, as well as destination managers have been actualized. behavior that a person is expected to perform. Such an award is a norm that can lead to a role, including the role of the government as a facilitator, the role of the government as a regulator, and a. the role of the government as a facilitator. This is also in accordance with the maktum. Regent Regulation Number 38 of 2016 concerning Position, Organizational Structure, Main Duties and Functions and Work Procedures Keywords: Creative Economy, Stakeholder Collaboration, Polewali Mandar.